Contemporary Polish geography through the lens of a national congress: thematic structure, interdisciplinarity and current research orientations - Mroczek, Przemysław; Jakubowski, Andrzej; Dobrowolski, Radosław; Uljasz, Barbara (Quaestiones Geographicae, 2026)
National scientiﬁc congresses provide community-deﬁned, time-sensitive material for examining the thematic organisation of academic disciplines. This paper analyses contemporary academic geography in Poland through contributions presented at the Congress of Polish Geography 2025 (Lublin), treating the ofﬁcial programme and published abstracts as a structured empirical corpus. A multi-level analytical framework combining programme-based classiﬁcation with qualitative thematic coding is used to identify dominant research domains, cross-cutting themes and patterns of integration. The results indicate a diversiﬁed yet internally coherent disciplinary structure in which interdisciplinarity is selective and organised around methodological and problem-oriented interfaces that help maintain thematic coherence.